Numerical Analysis for U-Shaped Thin-Walled Structure Reinforced Timber Beam Based on Thin-Layer Beam Theory - Hui Liu; Jun Hu; Guohui Li; Guangying Mo (Advances in Civil Engineering)
This paper presents a theoretical model, taking into account the shear deformation subjected to the influence of U-shaped member by geometric parameters as flange height based on thin-layer beam theory, to analyze the structural bending behavior of U-shaped member reinforced timber composite beams, and the feasible design forms of U-section have been pointed out. The algorithm for this composite beam is the most practical and effective method to meet the accurate solution. The formulas for the common forms of U-section are presented. It aims to develop a rational engineering approach. The proposed model has been validated by comparing the results obtained in the present analysis with experimental results and finite element analysis. Furthermore, the results suggested that the value of flange height can be one-fifth the beam height based on the present analysis by comparison of two types of beams. And it is shown that the model provided here correlates consistently and satisfactorily with a wide range of timber beams reinforced by a thin-walled structure such as steel or aluminum alloy sheet bonded to their tension faces.